Molecularly imprinted polymeric microspheres for electrochemical sensing of cholesterol - Ulianas, Alizar (Tanjung Malim, 2021)
Molecularly imprinted polymeric microspheres for electrochemical sensing of cholesterol by Ulianas, Alizar